2022
DOI: 10.20956/hajas.v4i1.20192
|View full text |Cite
|
Sign up to set email alerts
|

The Feed ADF and NDF Digestibilityof Goat Fed Four Difference Diets

Abstract: Goats generally have the ability to utilize carbohydrate sources from forages in the form of cellulose, hemicellulose, and pectin obtained from plant cell walls. Generally, forage contains relatively high crude fiber content which can be indicated by the contents of neutral detergent fiber (NDF) and acid detergent fiber (ADF) of the forage. The aim of this study was to examine the level of the feed consumption and digestibility of NDF and ADF of 4 different local forages fed to goats. This study was designed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The value of ADF and NDF can be used to determine the availability of fiber and the level of digestibility of a feed ingredient, where the lower the value of the NDF and ADF levels, the higher the digestibility of the feed. The lower the Neutral Detergent Fiber (NDF) and Acid Detergent Fiber (ADF) fractions, the higher the digestibility of the feed [11].…”
Section: Resultsmentioning
confidence: 99%
“…The value of ADF and NDF can be used to determine the availability of fiber and the level of digestibility of a feed ingredient, where the lower the value of the NDF and ADF levels, the higher the digestibility of the feed. The lower the Neutral Detergent Fiber (NDF) and Acid Detergent Fiber (ADF) fractions, the higher the digestibility of the feed [11].…”
Section: Resultsmentioning
confidence: 99%
“…The authors indicated that sorghum hull was used as a feed alternative for growing goats due to its benefits for growth performance, nutrient digestibility, and plasma metabolites. Goats were fed four different types of grasses, including Brachiaria-decumbens , Panicum maximum , Elephant grass , and Mini elephant grass , each at 80% plus 20% rice bran, according to a study by Ismartoyo et al [ 77 ]. In vivo neutral detergent fiber (NDF) and ADF digestibility were found to be 54 and 34.5%, 60 and 44%, 47.7 and 66%, and 27.5 and 48.9%, respectively.…”
Section: Alternative Feed Resources In Small Ruminant’s Nutritionmentioning
confidence: 99%